European Instructional Lectures Volume 13, 2013, 14th EFORT Congress, Istanbul, Turkey - Bentley, George (European Instructional Lectures, 2013)
This thirteenth volume in the EUROPEAN INSTRUCTIONAL LECTURES series continues the format of educational chapters from across Orthopaedics and Traumatology contributed by distinguished Orthopaedic Educators in Europe.   It provides current material and major advances covering a range of topics including:   ·       General Orthopaedics, Basic Science and Technology ·       Musculo-skeletal Tumours ·       Infections ·       Paediatric Orthopaedics ·       Trauma ·       Spine ·       Upper Limb ·       Hip ·       Knee ·       Leg, Ankle and Foot   All the lectures were presented at the 14th EFORT Congress in Istanbul, Turkey. The lectures are an authoritative source of information illustrated by radiographs, MRI and CT Scans, operative photographs, tables and line drawings. They are an invaluable source of instruction for Surgeons and Trainees alike. This book was edited by Professor George Bentley, Chairman, Scientific Publications Committee of EFORT.